Mapping Research Trend in Psychological Empowerment and Job Satisfaction in the Era of Industrial Revolution 5.0: A Bibliometric Analysis - Fika Wulan Meilana Putri; Sri Handari Wahyuningsih (Journal of Economics and Management Scienties, 2026)
In the context of Industry 5.0, which emphasizes the integration of advanced technology with human-centered values, psychological empowerment has emerged as an important factor in shaping an adaptive, flexible, and meaningful work environment. Understanding its relationship to job satisfaction is essential to improving organizational effectiveness. This study uses bibliometric analysis to map global research trends on psychological empowerment and job satisfaction. A total of 73 articles indexed in the Scopus database between 1994 and 2024 were analyzed using RStudio and VOSviewer to identify thematic patterns, keyword co-occurrence, and publication dynamics. The analysis reveals a consistent increase in academic interest in these topics over the past three decades. Psychological empowerment is often associated with increased job satisfaction, especially through mechanisms such as perceived autonomy, intrinsic motivation, self-efficacy, and workplace meaning. The co-emergence analysis further highlights a strong relationship with organizational commitment, leadership, and organizational culture. These findings confirm that in the Industry 5.0 era, synergy between technology and human empowerment is the main key in maintaining employee welfare. In addition, this research makes a practical contribution for managers in designing a more humanistic and adaptive human resource management strategy. This study also maps the direction of future research to deepen understanding of psychological dynamics in an increasingly digitized work environment.